Biological tissue adhesive for multiple use in the accident and emergency department. Issue 5 (1st September 2000) - Gerrard, Claire; Moore, Steve; Ryan, Brendan
Abstract : Objective— To assess the strength of the glue and microbial contamination over 28 days from opening a vial of tissue adhesive in the accident and emergency setting, and to quantify cost savings of repeated use of the vials. Method —(1) Strips of reinforced nylon and a specially constructed piece of apparatus designed to measure the force at which the glue gave way were used to measure the strength of the tissue adhesive at various times after the glue was opened to assess if the glue strength deteriorated over time. (2) Microbial contamination of the glue was assessed. Results —There was no deterioration in the glue strength over time. There was no evidence of microbial contamination of the glue. Conclusion —Cyanoacrylate tissue adhesive can safely be reused for a period of 28 days after opening with no risk of degradation of glue strength or contamination with micro-organisms. In our department this represents a potential saving of £5400 per year.